2017
DOI: 10.1007/s11010-017-3152-4
|View full text |Cite
|
Sign up to set email alerts
|

The overexpression of Hsp90B1 is associated with tumorigenesis of canine mammary glands

Abstract: Heat shock proteins (Hsp) are molecular chaperones that are responsible for protein folding and maintenance of cellular homeostasis. Hsp90, an important member of HSP family, has an important role in breast cancer. Glucose-regulated protein 94 (Grp94) is the endoplasmic reticulum paralog of Hsp90 encoded by Hsp90B1 gene. To test if this protein is overexpressed in dogs with mammary tumor, we estimated and compared its serum levels in healthy dogs and that of dogs with mammary tumors. Hsp90B1 mRNA expression wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…To date, more than 2000 microsatellite markers have been reported, and many of them have been assigned to linkage groups and specific chromosomes [4]. Some studies have reported a few biomarkers for the diagnosis and prognosis of CMT [19,20]. However, there is a lack of rapid, sensitive and specific biomarkers, which are required for the diagnosis of carcinogenesis in earlier stages.…”
Section: Discussionmentioning
confidence: 99%
“…To date, more than 2000 microsatellite markers have been reported, and many of them have been assigned to linkage groups and specific chromosomes [4]. Some studies have reported a few biomarkers for the diagnosis and prognosis of CMT [19,20]. However, there is a lack of rapid, sensitive and specific biomarkers, which are required for the diagnosis of carcinogenesis in earlier stages.…”
Section: Discussionmentioning
confidence: 99%
“…HSP90β was reported to promote endothelial cell-dependent tumor angiogenesis by increasing vascular endothelial growth factor receptor expression (33). Serum HSP90B1 levels were reported to be significantly elevated in dogs with mammary tumors compared with those in healthy controls (34). Another study demonstrated that HSP90B1 is an oncogenic chaperone in hepatocyte carcinogenesis (35).…”
Section: Discussionmentioning
confidence: 99%
“…The present panel of canine mammary tumor biomarkers are mostly non-specific that fail to aid early tumor detection. In the past, we have put considerable efforts in search of biomarkers for the diagnosis and prognosis of CMT [ 18 , 30 ]. So, in the line of thought to explore out a best suited panel of biomarkers for diagnosing mammary tumors we studied the mammaglobin-B gene, because a single biomarker is never 100% efficient to give a perfect conclusion.…”
Section: Discussionmentioning
confidence: 99%
“…RPS19 gene encodes for ribosomal protein S19 of the 40S ribosomal subunit. This gene had been used as valid internal control in earlier cancer studies [ 18 ]. Non template control was kept to check for non-specific amplification.…”
Section: Methodsmentioning
confidence: 99%